2007
DOI: 10.2105/ajph.2005.080184
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Healthcare Spending by the Poor and Chronically Ill in the Republic of Korea

Abstract: Out-of-pocket spending in Korea is regressive, because lower-income groups pay disproportionately more of their income compared with higher-income groups. Low-income individuals with multiple chronic conditions are particularly vulnerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 7 publications
6
50
0
3
Order By: Relevance
“…20 This experience is also contrary to the experiences of other countries, even those that have already achieved universal coverage. 21 How can we explain this finding? The evidence might suggest that poor house- holds do not recognize that they are ill and thus do not use health care; or, worse, that they are constrained from diverting their resources to pay for health care, thereby forgoing treatment when they become ill.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…20 This experience is also contrary to the experiences of other countries, even those that have already achieved universal coverage. 21 How can we explain this finding? The evidence might suggest that poor house- holds do not recognize that they are ill and thus do not use health care; or, worse, that they are constrained from diverting their resources to pay for health care, thereby forgoing treatment when they become ill.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…32 Basing health-care financing largely on out-of-pocket payment is regarded as both inefficient and inequitable. [33][34][35][36] The high out-of-pocket and high rates of catastrophic health expenditure and impoverishment in China suggest that the support provided by insurance has been surpassed by increased service volumes and charges. More worrying is the possibility that, without effective cost controls, the increased flow of government subsidies to insurance companies has actually helped increase service volumes and charges through provider-induced demand.…”
Section: Provider Payment Methods and Cost Containmentmentioning
confidence: 99%
“…South Korea has a national health insurance (NHI) system, which offers universal coverage to the country's population. However, it has been suggested that the medical safety net protecting individuals or households from financial risk due to illness is insufficient in South Korea [22]. In 2007, the average outof-pocket expenditure by South Korean citizens was 35.7% of the country's total health care spending, and the proportion of public expenditure to total health expenditure was 54.9%; one of the lowest such proportions among Organization for Economic Co-operation and Development (OECD) countries [23].…”
Section: Introductionmentioning
confidence: 99%